Special spherical mobile robot for planetary surface exploration: A review. (11th April 2023) - Li, Minggang; Sun, Hanxu; Ma, Long; Gao, Panpan; Huo, Dongshui; Wang, Zhantong; Sun, Ping
Considering the requirements of high scientific return, low cost, less complexity, and more reliability for the robot proposed by the extreme environment exploration task on the planet surface, this article comprehensively reviews the history of the special spherical robot used for extraterrestrial surface exploration and summarizes the environmental characteristics and task difficulties of different planet surface. This article compares the advantages of different types of ground spherical robots and points out the superiority of special spherical robots, such as omni-direction, airtightness, zero-radius turning, under-actuated, swarming, and lightweight. In addition, the research progress of special spherical robots for extraterrestrial exploration, such as wind ball, jumping ball, fly ball, ball with leg, pendulum driven ball, tensegrity structure, are reviewed respectively. Finally, the performance characteristics of all these robots are analyzed, their application scope given.